2007
DOI: 10.1364/oe.15.016141
|View full text |Cite
|
Sign up to set email alerts
|

In vivo functional imaging of human cone photoreceptors

Abstract: We evaluate a novel non-invasive optical technique for observing fast physiological processes, in particular phototransduction, in single photoreceptor cells in the living human eye. The method takes advantage of the interference of multiple reflections within the outer segments (OS) of cones. This self-interference phenomenon is highly sensitive to phase changes such as those caused by variations in refractive index and scatter within the photoreceptor cell. A high-speed (192 Hz) flood-illumination retina cam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
167
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(181 citation statements)
references
References 31 publications
7
167
4
Order By: Relevance
“…As noted in the Introduction, intrinsic optical signals from individual human cone photoreceptors have been measured by a number of groups (10)(11)(12)(13)(14). The advanced state of adaptive-optics OCT methodology for the human eye enables such cone-specific intrinsic optical signals to be characterized with great precision and sensitivity, and rapid advances in measurement and clinical applicability of human photoreceptor optophysiology can certainly be expected (71).…”
Section: Activation and Deactivation Of Phototransduction After Strongmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted in the Introduction, intrinsic optical signals from individual human cone photoreceptors have been measured by a number of groups (10)(11)(12)(13)(14). The advanced state of adaptive-optics OCT methodology for the human eye enables such cone-specific intrinsic optical signals to be characterized with great precision and sensitivity, and rapid advances in measurement and clinical applicability of human photoreceptor optophysiology can certainly be expected (71).…”
Section: Activation and Deactivation Of Phototransduction After Strongmentioning
confidence: 99%
“…OCT has been universally adopted in clinical ophthalmology to map human retinal layer structure (2) and is widely used for angiography of the eye (3) and heart (4,5) and for in vivo biopsy of skin and other tissues (6,7). Ocular OCT has also been used in vivo to measure "intrinsic optical signals" from the photoreceptor layer of the retina (8,9), including from individual human cone photoreceptors (10)(11)(12)(13)(14). In no case, however, has the molecular mechanism underlying an intrinsic optical signal been unequivocally identified.…”
mentioning
confidence: 99%
“…Thus, path length changes can be measured with exquisite precision down to fractions of a wavelength. Jonnal et al (6) elegantly used the photoreceptors themselves as a biological interferometer, building a flood illumination, adaptive optics ophthalmoscope where the two interfering paths were reflections from the proximal and distal ends of the photoreceptor outer segments (Fig. 1).…”
mentioning
confidence: 99%
“…1). The resulting oscillations in intensity after a light stimulus suggested that IOSs correlate with a change in the optical path length of the photoreceptors during phototransduction (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation